A linear complementarity method for dynamic analysis of bridges under moving vehicles considering separation and surface roughness. (1st July 2015) - Zhu, D.Y.; Zhang, Y.H.; Ouyang, H.
Highlights: One unified formulation was established for a vehicle-bridge dynamic system considering separation. The randomness of the rail roughness was considered. The conventional trial-and-error iterative process was avoided. The influence of separation and the possibility of separation were studied. Abstract: In the present paper, a linear complementarity method for a vehicle-bridge dynamic system considering separation and random roughness is established. By introducing the linear complementarity relationship between the relative displacement of the wheels and the bridge at the contact points, the dynamic interaction problem of the vehicle-bridge coupled system is transformed into a standard linear complementarity problem, and two models with different connection relations between the wheels and the bridge are proposed. The presented models characterize the system with one unified formulation whether the wheels separate from the bridge or not, and the conventional trial-and-error iterative process in numerical simulation is avoided. In the numerical examples, the proposed method is verified by comparing it with the conventional method, and it is found that the velocity, the vehicle to bridge mass ratio and the road roughness have a significant influence on separation. By considering a vehicle model of three rigid bodies with four wheels and the randomness of the rail roughness in train–track–bridge system, the possibility of separation and the expectation of the maximum separation distance at different velocities are studied. The results show that it is very useful to carry out a stochastic analysis of the system and consider the influence of separation in vehicle and bridge design.